Seedlac Manufacturing through Integrated Lac Processing Unit: An Industrial Product - Sharma, S.C.; Prasad, N.; Pandey, S. K. (Indian Forester, 2024)
Seedlac manufactured from sticklac using developed integrated small scale lac processing unit with different treatments to know the variation in yield, color parameters and quality parameters. Mean seedlac yield obtained for seedlac manufactured using developed unit with different treatments of washing agent did not show any appreciable difference while mean impurity content was found within the standard limit. Color parameters of the manufactured seedlac with integrated unit were better compared to seedlac manufactured using small scale lac processing unit with same treatment. Addition of higher amount of washing agent within permissible limit, improves the lightness, redness and yellowness of seedlac manufactured using developed integrated unit compared to seedlac manufactured using small scale lac processing unit. All the quality parameters of manufactured seedlac using developed unit with different treatment of washing agent were determined and found within the acceptable limit as per standard values IS: 6921 – 1973. Grain size of seedlac manufactured from sticklac through the developed integrated unit was found similar to grain size of seedlac manufactured through small scale lac processing unit and were in accordance with the specification IS: 6921 – 1973. Maximum water soluble lac dye (a by-product of lac industry) was recovered from wash water of 1st batch washing with more than 50% dye content and lighter in color.